Jenis, Potensi dan Nilai Ekonomi Hasil Hutan yang Dimanfaatkan Masyarakat sekitar Tahura Bukit Barisan - Faujiah Nurhasanah; Ridwanti Batubara; Oding Affandi (Program studi Kehutanan USU, 2012)
TAHURA Bukit Barisan represent a forest bunch which is have direct interaction between people and forest. Doulu and Jaranguda Village is around Tahura area. Therefore was conducted research to know type, potency and economic value of forest product which exploited by society around TAHURA. The method that is used to determine the respondent is snowball sampling method. Based on interview on responden, type of forest product which exploited by people around TAHURA area are regen bamboo, bulak bamboo, medical plant, honey and animal . The biggest Economics value at both village is Bamboo Regen exploiting equal to Rp.1.069.256.000,00. Forest provide a major contribution to public life. Key words : TAHURA, type, economic value, contribution